ISLAMIC INHERITANCE LAWS AND THEIR ECONOMIC IMPLICATIONS IN INDONESIA: A LEGAL AND FINANCIAL PERSPECTIVE - Suyono Arni; Meera Gupta; Sun Wei (Yayasan Adra Karima Hubbi, 2025)
Islamic inheritance laws, derived from Shariah principles, play a critical role in shaping wealth distribution and economic behavior in Muslim-majority countries like Indonesia. However, the implementation of these laws often faces challenges due to the coexistence of customary (adat) laws and national legal frameworks, leading to disputes and inefficiencies in wealth management. This study examines the legal and financial implications of Islamic inheritance laws in Indonesia, focusing on their impact on wealth distribution, family welfare, and economic development. The research aims to identify gaps in the current legal framework and propose recommendations for harmonizing Islamic inheritance laws with national regulations to enhance their economic effectiveness. Using a mixed-methods approach, this study analyzes legal documents, court rulings, and financial data, complemented by interviews with legal experts, religious scholars, and families affected by inheritance disputes. The findings reveal that while Islamic inheritance laws promote equitable wealth distribution, their implementation is often hindered by legal ambiguities, lack of public awareness, and resistance from customary law practitioners. These challenges result in prolonged disputes, unequal asset distribution, and reduced economic productivity. The study concludes that harmonizing Islamic inheritance laws with national legal frameworks and enhancing public education on inheritance rights are essential for maximizing their economic benefits.